2014
DOI: 10.1590/bjpt-rbf.2014.0049
|View full text |Cite
|
Sign up to set email alerts
|

Gait profile score and movement analysis profile in patients with Parkinson's disease during concurrent cognitive load

Abstract: Background: Gait disorders are common in individuals with Parkinson's Disease (PD) and the concurrent performance of motor and cognitive tasks can have marked effects on gait. The Gait Profile Score (GPS) and the Movement Analysis Profile (MAP) were developed in order to summarize the data of kinematics and facilitate understanding of the results of gait analysis. Objective: To investigate the effectiveness of the GPS and MAP in the quantification of changes in gait during a concurrent cognitive load while wal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 29 publications
(45 reference statements)
1
10
0
1
Order By: Relevance
“…However, the ability to perform such tasks simultaneously is limited in patients with PD 25 . The gait, for example, by having a rhythmic and automatic behavior, is generated mainly by subcortical systems, which makes it be carried out without great attentional demand.…”
Section: Discussionmentioning
confidence: 99%
“…However, the ability to perform such tasks simultaneously is limited in patients with PD 25 . The gait, for example, by having a rhythmic and automatic behavior, is generated mainly by subcortical systems, which makes it be carried out without great attentional demand.…”
Section: Discussionmentioning
confidence: 99%
“…These concise measures of gait quality were recently proposed by Baker et al ( 37 ) as a simplification of the GDI approach previously formulated by Schwartz and Rozumalski ( 32 ): in fact, using GPS instead of GDI has some advantages, such as the reduced set of parameters considered (9 vs. 15) and the fact that GPS can be decomposed into individual joint and plane scores (GVS). This approach was found effective in characterizing gait alterations in individuals with PD ( 38 , 39 ) as well as in those affected by other neurological and non-neurological diseases, thus demonstrating general validity and a broad spectrum of applications ( 40 42 ). Specifically, the GVS represents the root mean square (RMS) difference between the tested subject’s curve for a certain movement (e.g., knee flexion–extension) and a reference curve calculated as the mean value of tests performed on the unaffected subjects.…”
Section: Methodsmentioning
confidence: 97%
“…In another study by the same researchers [99], the GPS was employed to assess changes in gait kinematics in patients with PD when a concurrent cognitive task was added. They found that the GPS value increased under dual task conditions, thus indicating a significant alteration of gait pattern.…”
Section: Summary Of Measures Of Gait Kinematicsmentioning
confidence: 99%